Deep vein thrombosis in SARS-CoV-2 pneumonia-affected patients within standard care units: Exploring a submerged portion of the iceberg. Issue 194 (October 2020) - Pizzolo, Francesca; Rigoni, Anna Maria; De Marchi, Sergio; Friso, Simonetta; Tinazzi, Elisa; Sartori, Giulia; Stefanoni, Filippo; Nalin, Francesca; Montagnana, Martina; Pilotto, Sara; Milella, Michele; Azzini, Anna Maria; et al.
Graphical abstract: Unlabelled Image Highlights: An association between COVID-19 and venous thromboembolism (VTE) is now recognized. The prevalence of VTE is high in COVID-19 patients hospitalized in standard care units. The prevalence of VTE is high even though thromboprophylaxis and in patients estimated at low risk. A high index of suspicion for VTE is crucial in patients with SARS-CoV-2 infection.